Peningkatan Kompetensi Guru dalam Menyusun Soal Ulangan melalui Workshop di Sekolah Binaan Sektor 1 Indramayu - Ade Sulaeman (Jurnal Pendidikan Madrasah, 2021)
This research aims to improve the competence of teachers in arranging replay questions through workshop activities. through the Snowball Throwing Method. The subjects of the study were teachers of SMP Binaan in Sector 1 Indramayu Regency, Lesson Year 2018/2019. This study uses the School Action method through two cycles that include planning, implementation, observation, and reflection activities. The results showed that the implementation of workshops by school supervisors proved scientifically able to improve the competence of teachers in drafting test questions. The increase in the number of teachers who are able and good at drafting the question of replay by 30.76% to 69.23%. The quality of the replay question also increased by 7.69% to 84.61%. Workshop activities can improve the competence of teachers in arranging the replay question. In addition, there needs to be planning of the steps of organizing the workshop in order to attract attention and be applied by teachers in arranging the replay questions effectively and efficiently